Keraguan Kepada Tuhan pada Remaja - Muhammad Idrus (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2006)
This article is an effort to describe the  from childhood to adolescence. The Fowler’s theory  of faith development  is used as reference. The focus of this article is to answer the question of how children who already developed (learned from child) can later on show doubt in their religion. The failure to overcome the life crisis and social influence is believed to be the important of emergence of  the religious doubts. Keywords: Religious doubt, faith development, adolescence